2015
DOI: 10.9755/ejfa.2015.04.058
|View full text |Cite
|
Sign up to set email alerts
|

Impact of transport distance on stress biomarkers levels in dromedary camel (Camelus dromedarius)

Abstract: The welfare conditions of domestic animals during transport to the slaughterhouse are largely known able to influence the level of their stress, physiology and meat quality. Furthermore, the reaction of animals to stressors depends on the duration and intensity of these stressors. The objective of the study was to investigate the effect of transport distance on some blood physiological indicators of stress and biomarkers of oxidant stress in camels. Transport distances were categorized as short (72-80km), medi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
0
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(5 citation statements)
references
References 36 publications
1
0
0
Order By: Relevance
“…Again, captive environments in elephant camps (i.e., providing adequate housing and abundant diets) could mitigate oxidative stress impacts, as has been observed in a comparison between free-ranging and captive equids [12]. There was a positive association between catalase activity and the stress marker, fGCMs, which agrees with studies that showed increased catalase responses during physiological stress events [94,148], but it is not always consistent [149,150]. Few studies have been conducted on the association between blood parameters and oxidative stress markers.…”
Section: Discussionsupporting
confidence: 82%
“…Again, captive environments in elephant camps (i.e., providing adequate housing and abundant diets) could mitigate oxidative stress impacts, as has been observed in a comparison between free-ranging and captive equids [12]. There was a positive association between catalase activity and the stress marker, fGCMs, which agrees with studies that showed increased catalase responses during physiological stress events [94,148], but it is not always consistent [149,150]. Few studies have been conducted on the association between blood parameters and oxidative stress markers.…”
Section: Discussionsupporting
confidence: 82%
“…In the case of camels and other animals, cortisol has been used as an indicator of stress ( El-Khasmi et al ., 2015 ; Tajik et al ., 2016 ). This may explain the increase in serum cortisol levels observed in this study.…”
Section: Discussionmentioning
confidence: 99%
“…In camel, transportation stress can induce an increase of circulating levels of cortisol, lactate, glucose and MDA which is positively correlated with travel distance. 4,6 This response may be mediated by an activation of the hypothalamo-hypophyso-adrenal axis during transport stress and may reduce the preslaughter amount of glycogen then affect the postmortem biochemical evolution in muscle. The high impact of road transport distance on the intensity of OS responses has been reported by other research in domestic animals.…”
Section: Discussionmentioning
confidence: 99%
“…2 As a very stressful factor, road transport of camels to the slaughterhouse is able to induce a significant increase of circulating levels of cortisol and oxidant stress (OS) indicators 3,4 resulting in an increase of free radical generation 5 and showing a significant correlation with road transport distance. 6 Furthermore, the reaction to transport stress may have an impact on the quality of slaughtered animal meat and depends on the duration and intensity of this stressor. 7,8 The objective of the study was to investigate the effect of transport distance on the ultimate pH (pHu: 24h postmortem pH), and the levels of water, ash, glycogen, protein and OS indicators (MDA and CAT)in meat of dromedary camels.…”
Section: Introductionmentioning
confidence: 99%